Logic Colloquium 2004 2007
DOI: 10.1017/cbo9780511721151.013
|View full text |Cite
|
Sign up to set email alerts
|

An overview of modern universal algebra

Abstract: Abstract. This article, aimed specifically at young mathematical logicians, gives a gentle introduction to some of the central achievements and problems of universal algebra during the last 25 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Basic background in universal algebra for this section can be found in the text by Burris and Sankappanavar [8]. For a convenient and informative summary concentrating on the major developments of the past twenty years we recommend R. Willard's survey [74]. We shall focus on varieties.…”
Section: Applications: Residually Finite Varietiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Basic background in universal algebra for this section can be found in the text by Burris and Sankappanavar [8]. For a convenient and informative summary concentrating on the major developments of the past twenty years we recommend R. Willard's survey [74]. We shall focus on varieties.…”
Section: Applications: Residually Finite Varietiesmentioning
confidence: 99%
“…We have already noted that a residually small and finitely generated congruence modular variety is forced to be residually very finite. Hobby and McKenzie showed that a locally finite variety V satisfying a nontrivial congruence identity is already congruence modular [38, Theorems 9.18 and 10.4] (or see [74,Section 5.7]). This result has since been sharpened to remove the locally finiteness requirement (see Kearnes and Kiss [45, Theorem 9.5]).…”
Section: Applications: Residually Finite Varietiesmentioning
confidence: 99%
See 2 more Smart Citations